2017
DOI: 10.1186/s12967-017-1333-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 68Ga-PSMA-11 PET-CT with mpMRI for preoperative lymph node staging in patients with intermediate to high-risk prostate cancer

Abstract: BackgroundTo evaluate the diagnostic value of 68Ga-PSMA-11 PET-CT with multiparametric magnetic resonance imaging (mpMRI) for lymph node (LN) staging in patients with intermediate- to high-risk prostate cancer (PCa) undergoing radical prostatectomy (RP) with pelvic lymph node dissection (PLND).MethodsWe retrospectively identified 42 consecutive patients with intermediate- to high-risk PCa according to D′Amico and without concomitant cancer. Preoperative 68Ga-PSMA-11 PET-CT, pelvic mpMRI and subsequent robot as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 20 publications
2
64
4
Order By: Relevance
“…The results of this review highlight the high specificity and positive predictive value of 68 Ga-PSMA PET in detecting pelvic lymph node metastases. Most studies report a perpatient specificity of 90% or higher [10,11,13,[15][16][17]19]. This high specificity is a result of the high expression of PSMA in PCa and lymph node metastases, resulting in a high tumour to background ratio [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this review highlight the high specificity and positive predictive value of 68 Ga-PSMA PET in detecting pelvic lymph node metastases. Most studies report a perpatient specificity of 90% or higher [10,11,13,[15][16][17]19]. This high specificity is a result of the high expression of PSMA in PCa and lymph node metastases, resulting in a high tumour to background ratio [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies were included in this review that presented data on the sensitivity and specificity of 68 Ga-PSMA PET for detection of pelvic lymph node metastases in men with newly diagnosed PCa (Table 1, Fig. 1) [8, [10][11][12][13][14][15][16][17][18][19]. Two prospective studies, including a total of 63 patients, showed a per-patient sensitivity (range) and specificity (range) of 64-100% and 90-95%, respectively.…”
Section: Diagnostic Performance Of 68 Ga-psma Pet For Pelvic Lymph Nomentioning
confidence: 99%
See 1 more Smart Citation
“…68 Ga-PSMA-11 was synthesized using an ITG semiautomated module as described previously (27). One hour before scanning, all patients were intravenously injected with 68 Ga-PSMA-11 (median, 131.72 MBq; range, 130.6-177.6 MBq).…”
Section: Pet/ct Examination and Image Evaluationmentioning
confidence: 99%
“…Presurgical computerized tomography (CT) scan ormagneticresonance imaging (MRI) is helpful for LN staging, but withlimitedaccuracy [7].Prostate-speci c membrane antigen (PSMA)is a surface protein thatis expressed in almost normal prostatetissues, and its expressionlevel is higher in PCatissues [8]. Inrecent years, PSMA has been introducedinto positron emissiontomography (PET) imaging [9], 68 Gallium-PSMApositron emissiontomography/computerized tomography( 68 Ga-PSMA PET/CT) hasbeen proven to be better thanordinary imaging tests in detectingmetastaticPCa [10]. Relatedstudies have also shown that 68 Ga-PSMA PET/CT is moresensitive for recurrent PCa witha low prostate-speci c antigen(PSA) [11,12].…”
Section: Introductionmentioning
confidence: 99%